Optimizing Natural Light Distribution for Indoor Plant Growth Using PMMA Optical Fiber: Simulation and Empirical Study. (3rd June 2018) - Asiabanpour, Bahram; Estrada, Alejandra; Ramirez, Ricardo; Downey, Marisa S.
Abstract : Daylighting methods have evolved along with the impetus to reduce the total nonrenewable utility energy consumed by lighting. In general, daylighting systems are an efficient method of delivering light for indoor applications. However, there is little research looking specifically at indoor agriculture applications. Today, optical fibers are commonly used in various applications including imaging, lighting, and sensing. Our study simulated and tested the efficiency of an optical fiber daylighting system in an indoor environment. We tested the illumination performance of optical fibers and specifically looked at light intensity, light uniformity, and the spectrum of 20 mm and 3 mm optical fibers at five distances by offsetting a spectrometer. The scenarios were first modeled and tested using lighting simulation software. Similar settings were then empirically implemented and measured. The results showed that a difference in diameter had an effect on light intensity and light uniformity; the larger the diameter the better the light uniformity and light intensity. Further, the distance at which the spectrometer was placed in reference to the light source showed a relationship between both light intensity and light uniformity; the smaller the distance the more the intensity and the less the uniformity. Additionally, the experiments showed that sunlight intensity was 30 times and 140 times greater than optical fiber output intensity in the absence of any UV filter and presence of UV light, respectively.